STRATEGI PUBLIC RELATIONSPT. KERETA API INDONESIA (PERSERO) DALAM MEMPUBLIKASIKAN LAYANAN KERETA API TARIF KHUSUS - Octadiva, Myra; Hayat, Heni (Jurnal InterAct, 2018)
This article aims to find out the strategies used by PT. KAI in publishing Railway Services Special Rates for Gambir-Bekasi Relations and Pasar Senen-Bekasi. In this research the methodology used is qualitative with a constructivist paradigm and the process of data collection conducts interviews as primary data and written data records from PT. KAI and literature study as secondary data. In this study using a qualitative descriptive method that is describing the object under study by using informants as data sources. Then the data analysis techniques used are the Miles and Huberman models. The results of the study indicate that Public Relations of PT. KAI has carried out 9 steps of Strategic Planning for Public Relations Ronald Smith including using press releases, social media, organizational media, and xbanner. The strategy implemented has been running quite well and there are still shortcomings in its implementation.